1997
DOI: 10.3109/01913129709021942
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Carcinoid Tumor of the Larynx: An Immunohistochemical, Ultrastructural, and Flow Cytometric Analysis

Abstract: The clinicopathologic features, including a detailed immunohistochemical, ultrastructural, and flow cytometric analysis, are described in three cases of atypical carcinoid tumor of the larynx. All patients had metastatic disease within cervical lymph nodes at presentation and eventually developed distant metastases. Special stains revealed focal intracytoplasmic mucin accumulation, and immunohistochemistry showed the tumors to be positive for CAM 5.2, CEA, chromogranin A, and calcitonin. In two cases, double-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…22,23 In contrast, it has been suggested that p53, which has been shown to be diffusely positive in three laryngeal moderately differentiated neuroendocrine carcinomas, may play a role in the pathogenesis of this tumor, unlike other neuroendocrine tumors. 5 However, these findings have not been validated.…”
Section: Ttf-mentioning
confidence: 96%
See 2 more Smart Citations
“…22,23 In contrast, it has been suggested that p53, which has been shown to be diffusely positive in three laryngeal moderately differentiated neuroendocrine carcinomas, may play a role in the pathogenesis of this tumor, unlike other neuroendocrine tumors. 5 However, these findings have not been validated.…”
Section: Ttf-mentioning
confidence: 96%
“…Currently, serum calcitonin is the only objective means for distinguishing primary moderately differentiated neuroendocrine carcinoma of the larynx from metastatic medullary carcinoma, as calcitonin immunohistochemistry is reportedly positive in both tumors. [3][4][5][6] Thyroid transcription factor-1 (TTF-1) is a nuclear homeodomain transcription factor that is selectively expressed in developing respiratory epithelium, thyroid and diencephelon. 7,8 Immunohistochemical studies have shown that TTF-1 is expressed in a subset of lung and most thyroid neoplasms, including pulmonary neuroendocrine tumors and medullary carcinoma of the thyroid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on NCL is fragmented over numerous case reports and series of small sample size, often with contradicting results, making it difficult to decide on an appropriate treatment strategy. Consequently, physicians facing these tumors often resort to treatment paradigms developed for better known neoplasms (eg, squamous cell carcinoma).…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al (2004) 34 found that 3 of 6 patients with moderately differentiated laryngeal NECs were p53-positive. McCluggage et al (1997) 35 also reported that 3 atypical laryngeal carcinoid patients were p53-positive. Overholt et al (1995) 36 found that 6 of 8 patients with laryngeal neuroendocrine neoplasms (including 2 atypical carcinoids) were p53-positive.…”
Section: Discussionmentioning
confidence: 94%